Vector-Matrix Implementation of the Integrated Method of Recovery of Input Signals of Nonlinear Dynamic Systems (Моделювання, керування та інформаційні технології, 2020)
In the article the method of signal reconstruction at the input of nonlinear dynamic objects based on the application of vector-matrix approach to solving polynomial Volterra integral equations of the first kind of the second degree using a differential regularization operator is studied.